Training of specialized teachers and individualized educational planning: a research on perceptions - Amatori, Gianluca; Del Bianco, Noemi; Capellini, Simone Aparecida; Giaconi, Catia (Form@re - Open Journal per la formazione in rete, 2021)
The following paper is intended to conduct a reflection on the perception of teachers attending the specialization course for educational support activities for students with disabilities at the University of Macerata and the European University of Rome. In particular, the study presents an analysis of the perceptions on incoming skills of 54 teachers in training for specialization in preschools with the aim to highlight the topic of individualized educational planning, in relation to the recent ministerial changes relating to the new Individual Educational Plan (IEP) and to the dimensions connected to curricular teaching planning. Formazione degli insegnanti specializzati e progettazione educativa individualizzata: una ricerca sulle percezioni Il seguente contributo ha lo scopo di condurre una riflessione sulla percezione dei docenti frequentanti il corso di specializzazione per le attività di sostegno didattico agli alunni e alle alunne con disabilità presso l’Università degli Studi di Macerata e l’Università Europea di Roma. In particolar modo, lo studio presenta un’analisi delle percezioni sulle competenze in entrata di 54 docenti in formazione per la specializzazione nelle scuole dell’infanzia rispetto ai temi della progettazione educativa individualizzata, in relazione ai recenti cambiamenti ministeriali relativi al nuovo Piano Educativo Individualizzato (PEI) e alle dimensioni connesse alla progettazione didattica curricolare.